Descriptive Study of Government Expenditure & Poverty Reduction in South Halmahera, Indonesia (Maqashid Sharia Approach) - Inat, Fathy; Fadly, Fadly; Abubakar, Idrus; Rusdin, Firman (Jurnal Economia, 2024)
AbstractGovernment intervention plays an important role in reducing poverty in South Halmahera as an antithesis to when market mechanisms fail to distribute wealth. From the Islamic public finance perspective, the ulil-amri (the government) plays a central role in managing public budget and is subject to the sharia value system. This research descriptively explores how the SH government manages its expenditure side for poverty alleviation and tries to conceptualize direct spending using the 2019 APBD(The Regional Revenue and Expenditure Budget) sample with the maqashid sharia approach. The results show that government spending brings benefits to the poor, but unfortunately an increase in spending does not always reduce poverty. During the COVID-19 pandemic, budget refocusing was quite successful in reducing poverty. Meanwhile, the expenditure allocation according to the maqashid sharia indicator has reached 69% of the total direct expenditure, although the expenditure allocation for religious protection received the smallest portion, 0.42%. Keywords:Poverty, Government Expenditure, Budget Refocusing, Maqashid Sharia